Frösöns offerträd : En symbios av två kulturer? - Gillberg, Moa (Umeå universitet, Institutionen för idé- och samhällsstudier, 2021)
The sacrificial tree of Frösö: A symbiosis of two cultures? This bachelor thesis deals with the site of what has been interpreted as the remains of a sacrificial tree under the church of Frösö, on the island of Frösö. The found material consists predominantly of animal bones, where a large part has been identified as wild animals such as brown bears, but also a large number of juvenile pigs. Previous research has interpreted the place as an Old Norse place of worship to the Norse god Frey, due to the rich numberof pigs and the islands theophoric name (translated to “The island of Frey”). The unusual wild animals, such as squirrels and red deer have been interpreted as a staging of the ancient world tree Yggdrasil in Norse mythology. The overrepresentation of bones from brown bear however has been debated and is often compared to Sami bear graves. There are some similarities to the bear graves, but the differences that exist needs to be looked at more closely. The aim is to process materials and interpretations in a more holistic way. This is done by discussing various ritual acts, belief system and the choice of place of worship and sacrificial material, then apply this to the findings under the church of Frösö. Since such a large part of the bone material descents from brown bears, the use of bears in various cult practices has also been studied. The aim of this study is to provide new insight and interpretation of which ethnic groups may have used the site, before the church was built.The discussion concludes that a symbiosis is possible in the vicinity of the island, and that it is therefore not unlikely that this also applies to the island of Frösö. The found material under the church of Frösö could be remnants of a bear ceremony, but it could also be remnants from a more economic aspect or simply a mixture of the two. The bear was important financially in the Norse society and a Sami influence, based on their customs and beliefs, is not entirely unlikely given the close contact that existed. This could ...